2017
DOI: 10.1371/journal.pone.0177926
|View full text |Cite
|
Sign up to set email alerts
|

Automatic adventitious respiratory sound analysis: A systematic review

Abstract: BackgroundAutomatic detection or classification of adventitious sounds is useful to assist physicians in diagnosing or monitoring diseases such as asthma, Chronic Obstructive Pulmonary Disease (COPD), and pneumonia. While computerised respiratory sound analysis, specifically for the detection or classification of adventitious sounds, has recently been the focus of an increasing number of studies, a standardised approach and comparison has not been well established.ObjectiveTo provide a review of existing algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(140 citation statements)
references
References 107 publications
(134 reference statements)
0
124
1
Order By: Relevance
“…The discussion of these studies would expand beyond the scope of this article, and interested readers are therefore directed to recent reviews of respiratory sound analysis. [42][43][44] For the clinician, Another observation that may relate to interregional airflows is the capture of an inspiratory wheeze that continues uninterrupted into expiration ( Figures 6 and 7). The detection of this phenomenon requires simultaneous recording of sound and airflow.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussion of these studies would expand beyond the scope of this article, and interested readers are therefore directed to recent reviews of respiratory sound analysis. [42][43][44] For the clinician, Another observation that may relate to interregional airflows is the capture of an inspiratory wheeze that continues uninterrupted into expiration ( Figures 6 and 7). The detection of this phenomenon requires simultaneous recording of sound and airflow.…”
Section: Measurementmentioning
confidence: 99%
“…Over the past four decades, there have been numerous studies of computerized analyzes of wheezing, many with a focus on the engineering aspects of digital signal processing, and methods for pattern analysis and the automated detection of wheezes. The discussion of these studies would expand beyond the scope of this article, and interested readers are therefore directed to recent reviews of respiratory sound analysis . For the clinician, wheeze recording and analysis are of interest because they provide objective documentation and characterization of the adventitious sound, independent of perception and communication by observers.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have been done to detect wheeze [15]. However, to the best of our knowledge, this work is the first to present a reliable model for respiratory phase based wheezing detection and its application towards assessment of severity of the pulmonary condition.…”
Section: Introductionmentioning
confidence: 99%
“…This method is non-invasive and simple, however it is heavily dependent on the physical presence of a physician, the experience of the physician, sensitivity and variability of human auditory system [14], presence of noise in the internal or external environment, technical specifications and response efficiency of stethoscopes [4]. The following survey paper summarizes some interesting previous works done on wheezing detection [15]. Few of them attempted at wheezing detection against other adventitious sounds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there has been much research developed to detect DAS found in lung sounds. Recently, Pramono et al [13] presented a systematic review of automatic adventitious respiratory sound analysis. Regarding the analysis of crackles, they cited 36 papers that involve detection or classification and listed their data sources, amount of data, validation method, features used, classification method and performance.…”
Section: Machine Learning Approaches To Symptom and Pathology Detectionmentioning
confidence: 99%